Gender-based disparities on health indices during COVID-19 crisis: a nationwide cross-sectional study in Jordan - Mohammad Abufaraj; Zaid Eyadat; Mohammed Qussay Al-sabbagh; Abdullah Nimer; Immanuel Azaad Moonesar; Lin Yang; Walid Al Khatib; Ra’eda Al-Qutob (International Journal for Equity in Health, 2021)
Abstract Background COVID-19 has an inevitable burden on public health, potentially widening the gender gap in healthcare and the economy. We aimed to assess gender-based desparities during COVID-19 in Jordan in terms of health indices, mental well-being and economic burden. Methods A nationally representative sample of 1300 participants ≥18 years living in Jordan were selected using stratified random sampling. Data were collected via telephone interviews in this cross-sectional study. Chi-square was used to test age and gender differences according to demographics, economic burden, and health indices (access to healthcare, health insurance, antenatal and reproductive services). A multivariable logistic regression analysis was used to estimate the beta-coefficient (β) and 95% confidence interval (CI) of factors correlated with mental well-being, assessed by patients’ health questionnaire 4 (PHQ-4). Results 656 (50.5%) men and 644 (49.5%) women completed the interview. Three-fourths of the participants had health insurance during the COVID-19 crisis. There was no significant difference in healthcare coverage or access between women and men (p > 0.05). Half of pregnant women were unable to access antenatal care. Gender was a significant predictor of higher PHQ-4 scores (women vs. men: β: 0.88, 95% CI: 0.54–1.22). Among women, age ≥ 60 years and being married were associated with significantly lower PHQ-4 scores. Only 0.38% of the overall participants lost their jobs; however, 8.3% reported a reduced payment. More women (13.89%) were not paid during the crisis as compared with men (6.92%) (P = 0.01). Conclusions Our results showed no gender differences in healthcare coverage or access during the COVID-19 crisis generally. Women in Jordan are experiencing worse outcomes in terms of mental well-being and economic burden. Policymakers should give priority to women’s mental health and antenatal and reproductive services. Financial security should be addressed in all Jordanian COVID-19 national plans because the crisis appears widening the gender gap in the economy.